2016
DOI: 10.1167/iovs.16-20099
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Glaucoma Risk in Hyperlipidemic Individuals: A Critical Problem in Design

Abstract: Because glaucoma is the leading cause of irreversible visual impairment and is usually undetectable until advanced stages, 1 investigations on modifiable factors associated with glaucoma risk are warranted. The recent article by McCann et al., 2 which reported on a meta-analysis of observational studies evaluating the effects of statins on glaucoma, demonstrated that ''shortterm statin use is associated with a reduced incidence of glaucoma.'' This is, to our knowledge, the first comprehensive review of stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Carefully determining the association with hyperlipidemia is important to help evaluate the possibility of confounding by indication 37 where associations with cholesterol-lowering drugs, such as statins, have been reported. Consistent with other studies 26,38 (eg, a meta-analysis 26 reported an RR of 1.40 [95% CI, 0.73-2.68] for hyperlipidemia history), we observed a trend of higher risk of POAG with higher serum cholesterol levels. This finding indicates that if (1) statins truly lower the risk of POAG and (2) higher cholesterol levels are associated with elevated POAG risk and (3) higher cholesterol levels were associated with being prescribed more statins, then the confounding bias would have been toward the null.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Carefully determining the association with hyperlipidemia is important to help evaluate the possibility of confounding by indication 37 where associations with cholesterol-lowering drugs, such as statins, have been reported. Consistent with other studies 26,38 (eg, a meta-analysis 26 reported an RR of 1.40 [95% CI, 0.73-2.68] for hyperlipidemia history), we observed a trend of higher risk of POAG with higher serum cholesterol levels. This finding indicates that if (1) statins truly lower the risk of POAG and (2) higher cholesterol levels are associated with elevated POAG risk and (3) higher cholesterol levels were associated with being prescribed more statins, then the confounding bias would have been toward the null.…”
Section: Discussionsupporting
confidence: 91%
“…24 Furthermore, for some studies, confounding by indication due to hyperlipidemia (and concomitant hypertension and diabetes) has been raised as a concern, 25,26 and the association between hyperlipidemia and POAG has been unclear. 25,26 Our primary a priori hypothesis was that longer duration of statin use is associated with a lower risk of POAG, and our secondary hypothesis was that higher cholesterol levels are associated with a higher risk of POAG. Therefore, we examined the association of hyperlipidemia as well as statin use with risk of POAG among 50 710 women in the Nurses' Health Study (NHS), 62 992 women in the NHS2, and 23 081 men in the Health Professionals Follow-up Study (HPFS) followed up for 15 or more years.…”
mentioning
confidence: 99%
See 1 more Smart Citation